The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jvs.12302
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence of native and non‐native species influencing one another's abundance and distribution in the herb layer of an oak woodland

Abstract: Question: To what extent are species, including native and non-native species, influencing one another's distribution and abundance in the herb layer of a Minnesota oak woodland?Location: Oak woodland succeeding into a more mesic forest, on bluffland of the Mississippi River, east-central Minnesota. Methods:We collected plant composition and species cover data in 182 1.0 9 0.5 m quadrats regularly spaced on a 6-ha study grid in the oak woodland. We also recorded slope, slope position, aspect, elevation and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
2
20
1
Order By: Relevance
“…; Davis et al . ), most biological invasions result in significant negative ecological and economic impacts (Simberloff & Rejmánek ; Vitule et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…; Davis et al . ), most biological invasions result in significant negative ecological and economic impacts (Simberloff & Rejmánek ; Vitule et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In a prior study in the same site that did not differentiate quadrats based on density, we observed largely positive correlations among species and guilds, which we attributed to overlapping habitat preferences among herb species, including Alliaria (Davis et al. ). Our main motivation for differentiating quadrats based on cover in the present study was to attempt to isolate this possibility, which should generate positive correlations and be strongest at the lowest cover levels, from negative correlation‐generating mechanisms such as competition, which should be strongest at the highest overall cover.…”
Section: Discussionmentioning
confidence: 50%
“…Details of the location and ecology of the station have been described elsewhere (Davis et al. , ). Briefly, the woodland habitat is dominated by oak species (primarily Quercus rubra L., Q. ellipsoidalis E.J.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Garlic mustard co‐existing among native species of the herbaceous layer of a deciduous forest of east‐central Minnesota (Davis et al ., ). Note encircled cordate basal leaf in center, typical of vegetative first year of this obligate biennial (photograph credit: Mark Davis).…”
mentioning
confidence: 99%